Diphtheritic myocarditis: An unusual and reversible cause of heart failure - Balaji Arvind; Vineeta Ojha; Sudheer Kumar Arava; Sandeep Seth; Sivasubramanian Ramakrishnan (Wolters Kluwer Medknow Publications, 2022)
Diphtheria is a life-threatening infectious disease caused by Corynebacterium diphtheriae. Although the disease is seen infrequently in the postvaccination era, sporadic cases continue to occur. Cardiac involvement, in the form of myocarditis, is the most serious manifestation of diphtheria and is the most common cause of mortality in these patients. The features of diphtheritic myocarditis on cardiac magnetic resonance imaging (MRI) have not been reported previously. In this brief report, we describe the cardiac MRI and histopathologic features on endomyocardial biopsy of a patient with acute heart failure who was later diagnosed to be a case of diphtheritic myocarditis.